Energy drink doses of caffeine and taurine have a null or negative effect on sprint performance - Jeffries, O.; Hill, J.; Patterson, S. D.; Waldron, M. (The Journal of Strength and Conditioning Research, 2020)
This study investigated the effects of caffeine and taurine coingestion on repeat-sprint cycling performance and associated physiological and perceptual responses. In a double-blind, cross-over, repeated measures study, 11 male subjects (age 21 ± 2 years; stature 178 ± 7 cm; body mass 80 ± 13 kg) completed 10 × 6-second sprints on a cycle ergometer, each separated by 24 seconds, one hour after ingesting: caffeine (80 mg) and taurine (1 g), equivalent to the amount observed in popular commercial energy drinks, or placebo (maltodextrin ~1 g) in a gelatine capsule. Performance was measured on a cycle ergometer, whereas blood lactate concentration (B[la]), rating of perceived exertion (RPE), and heart rate (HR) were measured at baseline (pre-exercise) and after sprints 5 and 10. Magnitude-based inferences revealed likely, trivial differences in peak power and unclear, trivial intersprint fatigue index after ingestion of the caffeine and taurine supplement. Intrasprint fatigue was greater in the caffeine and taurine condition at sprint 10 (likely, small) and possibly smaller in sprints 6-9. The caffeine and taurine supplement had a likely large effect on HR at baseline (effect size = 0.94) and increases in B[la] after sprints 5 (likely small) and 10 (possibly small). There was no effect of the supplement on RPE (unclear, trivial). Administration of caffeine and taurine at doses equivalent to commercial energy drinks did not improve repeat-sprint cycling performance and seemed to induce greater fatigue within selected sprints, particularly at the end of the trial. This undesirable performance effect occurs in parallel with increased HR and glycolytic metabolic bi-products.